On the Effects of Mergers on Equilibrium Outcomes in a Common Property Renewable Asset Oligopoly - Hassan Benchekroun; Gérard Gaudet (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper examines a dynamic game of exploitation of a common pool of some renewable asset by agents that sell the result of their exploitation on an oligopolistic market. A Markov Perfect Nash Equilibrium of the game is used to analyze the effects of a merger of a subset of the agents. We study the impact of the merger on the equilibrium production strategies, on the steady states, and on the profitability of the merger for its members. We show that there exists an interval of the asset's stock such that any merger is profitable if the stock at the time the merger is formed falls within that interval. That includes mergers that are known to be unprofitable in the corresponding static equilibrium framework.
Keywords: C73; D43; L13; Q20; 330; mergers; dynamic games; oligopoly; common property; renewable resources